'Such a waste' – conflicting communicative roles of Dutch midwifery students in childbirth decision making. (September 2018) - Sanders, Prof. dr. José; de Vries, Prof. dr. Raymond; Besseling, Susanne; Nieuwenhuijze, Prof. Dr. Marianne
Abstract: Objective: In the Netherlands, the place of birth, birthing position, and pain relief are subject to preference-sensitive decisions of women, after counseling by their midwife. Dutch midwives are responsible for providing information and advice to guide pregnant women in such decisions. In this study we investigate how midwifery students, who are simultaneously committed to midwifery values and influenced by media culture, approach such preference-oriented communication in midwifery care . Design and setting: In-depth interviews and a focus group with seventeen Dutch midwifery students were conducted and analyzed applying a grounded theory approach. Findings: Student midwives are confronted with women who prefer a medical ("safe") and pain-free ("comfortable") birth. Such preferences reveal culturally induced priorities that form a threat to the bond of trust between midwives and women throughout the childbirth continuum. This development is felt personally by midwifery students, as an impact on each individual physiological birth, as well as professionally, as a threat to the midwifery values they acquire in their education. The interviews revealed that students have adopted distinctive communicative strategies to respond to media-driven values in childbearing women: Take Time and Listen; Counsel Neutral Information; and Safeguard from Negative Impact. Key conclusions and implications: Non-confrontational communication strategies allow midwifery students to build a trusting relationship with women, but the strategies are in part contradictory. Students experience inner tension due to decision outcomes that conflict with their midwifery values. Consequences for midwifery education are discussed.